INCOME OF THE POPULATION FROM SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP - Saydkhodjayeva Nigorakhon Ibaydullaevna (Modern American Journals, 2025)
The article is devoted to the study of the types of income of the population, their sources, the main factors influencing changes in sources, the system of new income indicators and its features for small businesses and private entrepreneurship. The article reveals that the rate of final consumption and accumulation differs in a number of its characteristics and their impact on the income of the population.
Keywords: Small business and private entrepreneurship, market economy, cash income, income in kind, income in kind from services, real income, profit, price index, rent, labor productivity, dividends, interest, primary income, national income, distribution, redistribution, final consumption, accumulation rate.